2020
DOI: 10.15420/cfr.2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Functional Capacity and Quality of Life After Implantation of a Durable Left Ventricular Assist Device

Abstract: Continuous-flow left ventricular assist devices (LVAD) are increasingly used as destination therapy in patients with end-stage heart failure and, with recent improvements in pump design, adverse event rates are decreasing. Implanted patients experience improved survival, quality of life (QoL) and functional capacity (FC). However, improvement in FC and QoL after implantation is not unequivocal, and this has implications for patient selection and preimplantation discussions with patients and relatives. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
(202 reference statements)
1
8
0
Order By: Relevance
“…As expected, the study confirmed that the mean peak exercise capacity of LVAD recipients was less than half of that of the controls, and the reduced pVO 2 observed in LVAD recipients the current study is well in line with earlier reports 10,19,20 as is the ventilatory inefficiency. 9 The patient population in the current study is generally comparable to the HF patients with moderate HF as described in the study by Mapelli 11 (pVO 2 between 12 to 16 ml/kg/min), but the VE/VCO 2 of in LVAD recipients in the current study was somewhat lower (i.e., ventilatory efficiency was better) compared with the unsupported HF patients.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the study confirmed that the mean peak exercise capacity of LVAD recipients was less than half of that of the controls, and the reduced pVO 2 observed in LVAD recipients the current study is well in line with earlier reports 10,19,20 as is the ventilatory inefficiency. 9 The patient population in the current study is generally comparable to the HF patients with moderate HF as described in the study by Mapelli 11 (pVO 2 between 12 to 16 ml/kg/min), but the VE/VCO 2 of in LVAD recipients in the current study was somewhat lower (i.e., ventilatory efficiency was better) compared with the unsupported HF patients.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies (7) have reported pVO 2 in LVAD recipients with values ranging from 9.9 (34) to 20.3 STUDY LIMITATIONS. Although the current study is strengthened by its multicenter design and the large sample size, some limitations remain.…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective multicenter study was designed to collect data for pVO 2 in LVAD recipients. Based on earlier published reports (described elsewhere [7]), 34 centers performing CPET in LVAD recipients, either as part of research projects or as standard of care, were identified and invited to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations